Cigarette Beetle, Lasioderma serricorne (F.) (Insecta: Coleoptera: Anobiidae) - Brian J. Cabrera (EDIS, 2002)
This document is EENY-227, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: July 2001.